PERAN DISIPLIN KERJA MEMEDIASI PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. MINISO INDONESIA - Savizqy, Enugya Dinnar; Ayu Sriathi, Anak Agung; Ketut Surya, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
Every company wants the best performance from its employees so that company goals are met. Performance is the end result of all duties and obligations carried out by employees who are carried out with dedication and responsibility. Several factors that influence an employee's performance are work motivation and work discipline. This study aims to analyze the role of work discipline mediating the effect of motivation on employee performance at PT. Miniso Indonesia Bali Area. This research was conducted at PT. Miniso Indonesia Bali Area with the number of samples taken as many as 38 employees and using a saturated sample. Data collection in this study was carried out by interview and questionnaire methods. The data analysis technique used is path analysis and sobel test. Based on the results of the analysis, it was found that work motivation has a positive and significant effect on work discipline, work motivation has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, work discipline is a variable mediating the effect of work motivation on employee performance.